Tacos for two - St. Amant, Betsy (Revell, a division of Baker Publishing Group, 2021)
"Rory Perez can't cook, but she inherited a taco food truck from her late aunt. Desperate for money to keep the family business, she goes up against her worst competitor in a festival competition-the man she's been anonymously flirting with online for weeks"--